Cancer patients with oral mucositis: challenges for nursing care - Sarah Nilkece Mesquita Araújo; Maria Helena Barros Araújo Luz; Grazielle Roberta Freitas da Silva; Elaine Maria Leite Rangel Andrade; Lívio César Cunha Nunes; Renata Oliveira Moura (Universidade de São Paulo, 2015)
OBJECTIVE: to analyze nursing care provided to cancer patients with oral mucositis based on the Nursing Process (NP). METHOD: this exploratory, descriptive, cross-sectional and quantitative study was conducted with 213 patients undergoing chemotherapy and/or radiotherapy in two cancer facilities: one philanthropic and one private service. RESULTS: the participants were mainly female, aged 45.8 years old on average, with up to 11 years of schooling and income of up to one times the minimum wage. Severe mucositis was related to chemotherapy associated with radiotherapy. Only 25.3% of the patients reported having received guidance from nurses during their treatment concerning self-care. The perceptions of patients regarding quality of care did not significantly differ between the private and public facilities. The basic human needs mainly affected were comfort, eating, and hygiene. Based on this finding, one NP was established listing the diagnoses, interventions and expected results to establish an ideal, though individualized, standard of nursing care to be provided to these patients. CONCLUSION: to understand oral mucositis is crucial to establish nursing care that includes prevention based on the implementation of an oral care plan.